The Phenomena of Premium Khamr in Specific Point of View - Iskandardyah Siregar; Lyudmila Demidyuk (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article presents research that focuses on utilising cultural science concerning Premium Khamr. It initially examines how sociologists perceive drinking and compares it with their perspectives on music and the arts. The article discusses the complex interplay between a fondness for Premium Khamr and a sceptical stance towards the drinking culture phenomenon. The main focus of this paper revolves around proposing the development of a cultural science of Premium Khamr, drawing on a conceptualisation of long-term processes within cultural science. The study identifies various production and fabrication processes and their interactions, forming a comprehensive framework for the cultural science of Premium Khamr. To support the significance of this research, a phenomenological approach is employed to explore the understanding of psychological conditions, physiological impacts, and market contexts related to reading and comprehension